Review of private agricultural advocacy groups in Nigeria - Onyekuru, Anthony NwaJesus (International Food Policy Research Institute, 2010)
Public-private sector dialogue in Nigeria's economic policymaking process is fragmented and unstructured. As a result, the private sector has moved to organize itself around trade groups, which have the tendency to seek self-interest. Advocacy groups can help bring balance in private-public sector dialogue. This paper explores agricultural advocacy groups in Nigeria as instruments for economic policy change by focusing on their organization, functions, achievements, constraints, and sustainability.